Efecto del soporte sobre las propiedades texturales y catalíticas de catalizadores de Pd soportado. - Bastos, Annie; Finol, Dora; Méndez, Jonathan; Domínguez, Francisco; Rodríguez, Douglas; Ferrer, Víctor (Ciencia)
Ver resumen pdf.